Implementation of Transparency and Accountability in Village Fund Management to Support Covid-19 Prevention (Study in Sumberkedawung Village, Leces District, Probolinggo Regency) - Marwiyah, Siti; Puspitarini, Renny; Maulana, Rifki (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Every management of village funds needs to apply the principles of transparency and accountability. Government accountability has three main objectives, namely accountability, managerial, and supervision. Accountability by the government is a manifestation of providing information regarding every action or activity and financial management carried out by the government during implementation in a transparent manner. This study aimed to identify and describe the application of transparency and accountability in the management of village fund allocations in support of the prevention of Covid-19 in Sumberkedaung Village. This study used descriptive qualitative method. The selection of informants was deliberately selected who were considered to understand the matter to be studied, taking data from sources deemed relevant according to the issues and themes raised, so as to produce reliable data and determine the accuracy of research results. This study used the theory of policy implementation Matland Matrix which need to be met in terms of the effectiveness of policy implementation consisting of four components, namely Policy Accuracy, Implementation Accuracy, Target Accuracy, and Adjusted Environmental Accuracy. Based on indicators of accountability and transparency according to Permendagri Number 113 of 2014 concerning Village Financial Management which included planning, implementation, reporting and accountability. This research showed that the policies made and implemented were in accordance with the strategy for overcoming Covid-19 in Sumberkedawung Village